Congenital Amusia (or Tone-Deafness) Interferes with Pitch Processing in Tone Languages - Tillmann, Barbara; Burnham, Denis; Nguyen, Sebastien; Grimault, Nicolas; Gosselin, Nathalie; Peretz, Isabelle (Frontiers in Psychology, 2011)
Congenital amusia is a neurogenetic disorder that affects music processing and that is ascribed to a deficit in pitch processing. We investigated whether this deficit extended to pitch processing in speech, notably the pitch changes used to contrast lexical tones in tonal languages. Congenital amusics and matched controls, all non-tonal language speakers, were tested for lexical tone discrimination in Mandarin Chinese (Experiment 1) and in Thai (Experiment 2). Tones were presented in pairs and participants were required to make same/different judgments. Experiment 2 additionally included musical analogs of Thai tones for comparison. Performance of congenital amusics was inferior to that of controls for all materials, suggesting a domain-general pitch-processing deficit. The pitch deficit of amusia is thus not limited to music, but may compromise the ability to process and learn tonal languages. Combined with acoustic analyses of the tone material, the present findings provide new insights into the nature of the pitch-processing deficit exhibited by amusics.